A micro‐jet array for economic intensification of gas transfer in bioreactors. (9th October 2018) - Turney, D. E.; Ansari, M.; Kalaga, D. V.; Yakobov, R.; Banerjee, S.; Joshi, J. B.
Abstract : Bioreactors are of interest for gas‐to‐liquid conversion of stranded or waste industrial gases, such as CO, CH4, or syngas. Process economics requires reduction of bioreactor cost and size while maintaining intense production via rapid delivery of gases to the liquid phase (i.e., high k L a ). Here, we show a novel bioreactor design that outperforms all known technology in terms of gas transfer energy efficiency ( k L a per power density) while operating at high k L a (i.e., near 0.8 s −1 ). The reactor design uses a micro‐jet array to break feedstock gas into a downward microbubble flow. Hydrodynamic and surfactant measurements show the reactor's advanced performance arises from its bubble breakage mechanism, which limits fluid shear to a thin plane located at an optimal location for bubble breakage. Power dissipation and k L are shown to scale with micro‐jet diameter rather than reactor diameter, and the micro‐jet array achieves improved performance compared to classical impinging‐jets, ejector, or U‐loop reactors. The hydrodynamic mechanism by which the micro‐jets break bubbles apart is shown to be shearing the bubbles into filaments then fragmentation by surface tension rather than "cutting in half" of bubbles. Guided by these hydrodynamic insights, strategies for industrial design are given. © 2018 American Institute of Chemical Engineers Biotechnol. Prog ., 35: e2710, 2019